Downregulation of microR-147b represses the proliferation and invasion of thyroid carcinoma cells by inhibiting Wnt/β-catenin signaling via targeting SOX15. (5th February 2020) - Xu, Chongwen; Liu, Junsong; Yao, Xiaobao; Bai, Yanxia; Zhao, Qian; Zhao, Ruimin; Kou, Bo; Li, Honghui; Han, Peng; Wang, Xuan; Guo, Longwei; Zheng, Zhiwei; et al.
Abstract: microRNA-147b (miR-147b) is a newly identified tumor-related miRNA that is dysregulated in multiple cancer types. Yet, the role of miR-147b in thyroid carcinoma remains unknown. Herein, we found that miR-147b expression was upregulated in thyroid carcinoma tissues and cell lines. miR-147b inhibition decreased the proliferation, colony formation, and invasion of thyroid carcinoma cells. The tumor suppressive gene SRY-related high-mobility-group box gene 15 (SOX15) was predicted as a miR-147b target gene. SOX15 expression was markedly decreased in thyroid carcinoma tissues and inversely correlated with the miR-147b expression. SOX15 overexpression repressed the proliferation and invasion of thyroid carcinoma cells associated with downregulation of Wnt/β-catenin signaling. SOX15 knockdown abolished the miR-147b-inhibition-mediated antitumor effect. miR-147b inhibition or SOX15 overexpression retarded the tumor growth of thyroid carcinoma cells in vivo . Overall, our study suggests that miR-147b inhibition restrains the proliferation and invasion of thyroid carcinoma cells through upregulation of SOX15 and inhibition of Wnt/β-catenin signaling. Graphical abstract: Image 1 Highlights: miR-147b expression is upregulated in thyroid carcinoma. SOX15 expression is decreased in thyroid carcinoma. SOX15 is a target gene of miR-147b. Upregulation of SOX15 by inhibiting miR-147b exerts antitumor effect. miR-147b regulates Wnt/β-catenin signaling via targeting SOX15.